Women and the Nazi East : agents and witnesses of Germanization / Elizabeth Harvey. - Harvey, Elizabeth (Yale University Press, 2003)
Drawing on material from Polish and German archives, as well as memoirs and oral testimony from German women who were sent to wartime Poland, Elizabeth Harvey analyses the function of female activism within Nazi imperialism, its significance, and women's response to policies intended to segregate and persecute.